Al Isabah fi Tamyiz al Sahabah - Imam Ahmad Ibn Ali Ibn-Hajar-al-'Asqalaniy (Dar al Kutub al 'Ilmiyyah, 2002)
ws.jl.1-9.c.1/stoc4, jil.1-9,c.1-2; jil.1[jz.1-2]; jil.2 [jz.3-4], jil.3 [jz.5-6]; jil.4 [jz.7-8]; jil. [faharis], c.1